Tunable gelatin methacrylate polyethylene glycol diacrylate hydrogels for cell mechanosensing applications - Ferchichi, Eya; Stealey, Samuel; Bogert, Paige; Zustiak, Silviya Petrova (Frontiers in Biomaterials Science, 2024)
Three-dimensional (3D) tissue-engineered scaffolds mimic the physiological environment of cells by providing essential structural support, biochemical cues, and the mechanical strength needed for cell adhesion, proliferation, migration, and differentiation. Hydrogels like polyethylene glycol diacrylate (PEGDA) are commonly used biomaterials for cell culture due to their affordability, tunable stiffness, and ability to efficiently transport nutrients and gases. However, PEGDA lacks cell adhesion sites essential for cell proliferation and migration and has limited degradability. Methacrylated gelatin (GelMA) produced from denatured bovine collagen, crosslinks under ultraviolet light (UV) resulting in a degradable hydrogel with cell adhesion sites. Here, we synthesized GelMA with variable degree of methacrylation and crosslinked it with PEGDA to produce cell scaffolds with independently tunable mechanical and biochemical properties by varying the ratios of the two polymers. We determined polymer ratios that resulted in scaffolds with different mechanical properties but the same gelatin concentrations (providing cell adhesion and degradation sites) as well as different gelatin concentrations but the same mechanical properties. With the developed scaffold library, we further used a design of experiments approach to probe the parameter space and perform detailed analysis on chemical composition-scaffold properties as well as scaffold properties-cell behavior correlations. We suggest that such analysis will broaden the utility of the GelMA/PEGDA hydrogels, presenting a versatile platform for mechanosensing research in 3D environments.